UJI DAYA KEMBANG DAN UJI ORGANOLEPTIK KERUPUK SUKUN (Artocarpus altilis) DENGAN PENAMBAHAN TEPUNG YANG BERBEDA - Ayu Susilawati; Vita Kurnia Utami; Ulfa Maulida Farid (Teknologi Hasil Pertanian, Fakultas Teknik, Universitas Annuqayah, 2024)
Breadfruit (Artocarpus alitilis) is a multi-functional plant because it is used as traditional medicine and an alternative food source. The use of breadfruit is generally limited to serving it in the form of fried foods and vegetables, so food diversification must be carried out for a longer shelf life and to increase its high selling value and be suitable for consumption, namely processing it into breadfruit crackers. The aim of this research is to determine the effect of breadfruit crackers (Artocarpus altilis) with the addition of different flours on the swellability of the crackers and to determine the effect of the organoleptic properties of breadfruit crackers (Artocarpus altilis) with the addition of different flours. The research method used a Completely Randomized Design (CRD) with 3 treatments and 6 replications, namely P1: 50% breadfruit + 50% T. tapioca, P2: 50% breadfruit + 50% T. rice and P3: 50% breadfruit + 50% T. cornstarch. Data analysis used Paired Sample T-Test to test flowering power and organoleptic tests using One Way Anova and Duncan's advanced test. Based on the Paired Sample T-Test P1, P2 and P3, the results were significant at p < 0.05, so the treatment carried out in this study had a significant influence on the swelling power of breadfruit crackers. Meanwhile, based on the results of color, taste and texture analysis tests, it produced a significant value of p > 0.05 and it was said that there was no real difference to breadfruit crackers. Meanwhile, the significance of the aroma of breadfruit crackers is p < 0.05 and it can be said that there is a real difference to breadfruit crackers and can be tested further with the Duncan test which produces P3 with P1 and P2, there is a real difference to the aroma of breadfruit crackers.